2021
DOI: 10.1007/s41685-020-00180-6
|View full text |Cite
|
Sign up to set email alerts
|

Empirical exploration of remittances and renewable energy consumption in Bangladesh

Abstract: In recent years, a surge of remittances to Bangladesh has enabled rural households to adopt modern renewable energy sources. However, researchers have yet to examine any statistical association between remittances and renewable energy. In this study, we determined the causal relationships between per capita remittance inflows and renewable energy consumption in Bangladesh using annual data for the period 1980-2017. This is the first such study. This determination was made while controlling for changes in GDP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 73 publications
(103 reference statements)
5
18
0
Order By: Relevance
“…Thus, reflecting on the seemingly dormant role of the remittance, a significant contributor to Nepal's GDP, in the biomass consumption, and the negative elasticity of fossil fuel consumption from remittance in the ARDL model indicates the role it can play in the clean energy transition. Remittance is found to have a direct causality relationship with renewable energy consumption (Das et al 2021). Therefore, as a policy insight, we suggest that the remittance, which is a source of income for 24% of households in Nepal (Takenaka et al 2020), can be utilized for upscaling of the modern renewable energy technologies, share of which is below world's average in most LDCs, including Nepal.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, reflecting on the seemingly dormant role of the remittance, a significant contributor to Nepal's GDP, in the biomass consumption, and the negative elasticity of fossil fuel consumption from remittance in the ARDL model indicates the role it can play in the clean energy transition. Remittance is found to have a direct causality relationship with renewable energy consumption (Das et al 2021). Therefore, as a policy insight, we suggest that the remittance, which is a source of income for 24% of households in Nepal (Takenaka et al 2020), can be utilized for upscaling of the modern renewable energy technologies, share of which is below world's average in most LDCs, including Nepal.…”
Section: Discussionmentioning
confidence: 76%
“…The respondents from the government organisations mentioned increasing allocation of climate mitigation-related finance from government sources but did not mention leveraging the immense potential to mobilise the remittances, given its one-fourth share in the GDP in 2020 (World Bank 2021 ). Das et al ( 2021 ) have identified a long-run causality between remittance and renewable energy consumption, meaning that the remittance can be used to stimulate household-level renewable energy technologies that can replace biomass and fossil fuels to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…The domestic material consumption of Nepal is largely biomass-based (WU 2019 ), and therefore, any changes in the energy system, notably the rural energy transition (e.g. use of the solar home system, micro-hydro, and biogas) driven by remittances and ODA inflows (Das et al 2021 ) will contribute to the nation’s climate mitigation goals.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, they can be employed as shading devices. Power and daylight are supplied to the building or the grid, which provides a portion of the facility's lighting requirements [52].…”
Section: Integration Of Renewable Energy (Solar System)mentioning
confidence: 99%
“…Photovoltaic technology makes it possible to integrate solar panels into buildings. However, using materials in PV systems can cause some environmental and health risks regarding solar panel difficulties, such as dust concerns [52].…”
Section: Photovoltaic (Solar) Powermentioning
confidence: 99%